An equation is shown below:

4(x − 3) − 5(x + 1) = 3

Which statement shows a correct next step in solving the equation?

The equation can become 4x − 3 − 5x + 1 = 3 by applying the associative property of multiplication.
The equation can become 4x − 3 − 5x + 1 = 3 by applying the distributive property.
The equation can become 4x − 12 − 5x − 5 = 3 by applying the distributive property.

Respuesta :

Answer:

The equation can become 4x − 12 − 5x − 5 = 3 by applying the distributive property.

Step-by-step explanation:

By applying the distributive law to this equation, we can produce the equation :

     4x − 12 − 5x − 5 = 3;

The distributive property is a mathematical function in which each element in the parentheses is multiplied by the one outside of it;

   4(x − 3) − 5(x + 1) = 3

In the equation;

  4 distribute over the first parentheses and -5 over the second one;

   So we expand;

      4x - 13 - 5x -5  = 3

In distributive property, expansion simply takes place.